Women’s Drudgery and Maize Sheller Intervention: A Case of Tribes of Jaunsar Region of Uttarakhand - Joshi, Kushagra; Pandey, B M; Khulbe, R K; Pattanayak, Arunava (Indian Journal of Hill Farming, 2018)
The seemingly simple act of removing the grains from maize cobs by hand is not easy as it sounds. Maize shelling is a tedious task which poses many physical hazards to the worker involved in the task. This risk increases many-a-folds in the regions where maize is grown as a cash crop as the intensity of task and workload increases during the particular season. Shelling maize manually is a task which seems very simple and convenient and it is assumed that it is an activity that is usually done in spare time. But the experiences of the worker involved in this activity reports the hazards and stress which this act poses to them. The present study is an attempt to record the potential biomechanical stress and occupational hazards perceived by the farmwomen of Jaunsar region of Uttarakhand and the role of power operated maize sheller intervened in mitigating these threats. The perceptions of women using the maize sheller were recorded before and after the intervention and the difference were found statistically significant. The findings exhibited an encouraging impact of the technology on women’s efforts, time and discomfort.